Unravelling the mode of action of the Tres Cantos Antimalarial Set (TCAMS): investigating the mechanism of potent antimalarial compounds potentially targeting the human serotonin receptor - Benedito Matheus dos Santos; Lenna Rosanie Cordero Mallaupoma; Mateus Fila Pecenin; Abhinab Mohanty; Angela Lu; Paula J. Bartlett; Andrew P. Thomas; Francisco-Javier Gamo; Celia R. S. Garcia (Malaria Journal)
Abstract Background Despite the strides made in recent decades, the resistance observed in existing antimalarial drugs, and the intricate life cycle of the Plasmodium parasite underscore the pressing need to develop novel and effective therapeutic interventions. This article provides a comprehensive evaluation of the outcomes stemming from screening a library comprising 48 compounds (TCAMS) against Plasmodium falciparum. Methods This study focused on characterizing the IC50 values of compounds from the Tres Cantos Antimalarial Set (TCAMS) library via a double-labelling method of P. falciparum parasites with SYBR Green-I and MitoTracker Deep Red, which were evaluated via flow cytometry. Evaluation of the cytotoxicity of the best candidates in human embryonic kidney (HEK293) cells, chemoinformatic analysis, and exploration of the effects of the compounds on the action of serotonin and melatonin in the erythrocytic life cycle of the parasite. Results IC50 characterization confirmed that 93.75% of the compounds tested exhibited antimalarial activity at concentrations below 2 micromolar (µM), with 5 compounds showing IC50 values below 50 nM (nM) (15.21 ± 5.97 nM to 45.82 ± 5.11 nM). Furthermore, 12 compounds presented IC50 values between 50 and 100 nM (57.43 ± 12.25 nM to 100.6 ± 22.89 nM), highlighting their potent in vitro efficacy against P. falciparum. Cytotoxicity evaluation in HEK293 cells revealed that 12 from 17 compounds did not significantly reduce cell viability. Cheminformatics analysis clustered the compounds based on structural and physicochemical similarities, revealing distinct structural patterns. Exploration of hypothetical targets from the TCAMS library identified 27 compounds with potential targets, 15 specifically targeted serotonergic receptors. Subsequent serotonin and melatonin treatment experiments indicated that certain compounds could inhibit both effects on parasitaemia, suggesting a complex interaction with signaling in P. falciparum. Conclusions This study identifies promising antimalarial candidates with low IC50 values and highlights the significance of targeting serotonin receptors in the development of potential antimalarial drugs.